Energy Optimization of Combustion Process in Carbonization Chamber via Computational Fluid Dynamics (CFD) Approach - Ahmad Kujaji, Muhammad Hilmi (Universiti Teknologi PETRONAS, 2016)
Palm kernel shells is regarded as potential feedstock for the production of bio char due to its high lignin composition through carbonization process. Lots of studies have provided scientifically proven data that consistent with such statement. One of primary concerns during the production process is heat transfer and temperature distribution within the process reactor. Even small deviation from process parameter can affect the bio char production especially its quality and yield. Therefore, there is a need to perform optimization study to determine the best practice and methods in obtaining uniform heat transfer and temperature distribution. In this project, all analysis will be carried out using computational fluid dynamics (CFD) software, ANSYS CFX 15.0.